Prey - Vincent, Rachel (Don Mills, Ont. : MIRA, 2009)
"Sometimes playing cat and mouse is no game... Play? Right. My Pride is under fire from all sides, my father's authority is in question and my lover is in exile. Which means I haven't laid eyes on Marc's gorgeous face in months. And with a new mother and an I-know-everything teenager under my protection, I don't exactly have time to fantasize about ever seeing him again. Then our long- awaited reunion is ruined by a vicious ambush by strays. Now our group is under attack, Marc is missing and I will need every bit of skill and smarts to keep my family from being torn apart. Forever."--p. [4] of cover.
Includes preview of title "My soul to take", (p. [387]- 394).
Keywords: Supernatural -- Fiction; Metamorphosis -- Fiction; Families -- Fiction; Man-woman relationships -- Fiction; Fantasy fiction; Occult fiction